Nurse-coordinated home-based cardiac rehabilitation for patients with heart failure: A scoping review - Tiantian Ruan; Mengqi Xu; Lingyan Zhu; Yuan Ding (International Journal of Nursing Sciences, 2023)
Objectives: This study aimed to review and summarize the studies of nurse-coordinated home-based cardiac rehabilitation for patients with heart failure. Methods: The review was performed using Arksey and O’Malley’s scoping review framework. A systematic search was conducted across eight databases, including PubMed, Embase, Web of Science, EBSCO, China Biomedical Literature Service System (SinoMed), China National Knowledge Infrastructure (CNKI), Wanfang Database, and Chinese Science and Technology Journals (CSTJ) Database, and Chinese Clinical Trial Registry, from inception to 30 April 2023. Articles relevant to the nurse-coordinated home-based cardiac rehabilitation for patients with heart failure were included. Results: Eighteen studies were included in this review. These studies showed that nurses primarily focused on patient assessment, home-based cardiac rehabilitation planning and guidance, and follow-up. The studies also reported positive outcomes in patient safety, feasibility, and efficacy of the programs coordinated by nurses. Conclusions: Home-based cardiac rehabilitation coordinated by nurses is beneficial to patients with heart failure. Future research will explore the potential of nurses in home-based cardiac rehabilitation for patients with heart failure, determine optimal evaluation criteria, and formulate safe, effective, and economical rehabilitation programs suitable for the patients.